2015
DOI: 10.1007/s13197-015-1713-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient profile of porridge made from Eleusine coracana (L.) grains: effect of germination and fermentation

Abstract: Porridge (koozh) is one of the traditional foods made from Eleusine coracana L. grains (Finger millet). It is a soft food prepared from processed (germinated & fermented) finger millet flour (FMF). However, in the modern world of fast food, koozh is usually prepared from non-processed (non-germinated & non-fermented) FMF. Hence, present study was undertaken to evaluate the macro and micro nutrient contents in koozh prepared from germinated (fermented & non-fermented) and non-germinated (fermented & non-ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Subastri et al . ( 31 ) in their study on koozh (a porridge made from germinated and fermented finger millet) reported an increased amino acid, phytochemical and free radical scavenging activity. In the case of a fermented milk with added millet, the bioactive peptides and amino acids from the milk proteins derived through fermentation might also have contributed to the positive role of finger millet polyphenols towards regulation of postprandial glycaemia and amelioration of complications related to diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Subastri et al . ( 31 ) in their study on koozh (a porridge made from germinated and fermented finger millet) reported an increased amino acid, phytochemical and free radical scavenging activity. In the case of a fermented milk with added millet, the bioactive peptides and amino acids from the milk proteins derived through fermentation might also have contributed to the positive role of finger millet polyphenols towards regulation of postprandial glycaemia and amelioration of complications related to diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional processing of FM food products has received poor scientific applications especially in the developing countries. Thus, the use of modern processing technology in the manufacture of commercial products from FM is required (Saleh et al, 2013;Subastri et al, 2015).…”
Section: Processing Methods Of Finger Millet Grainsmentioning
confidence: 99%
“…Finger millet grains are also reported to be associated with lowering the risk of diabetes, reduction of blood pressure and cardiovascular diseases (Pradeep & Sreerama, 2015). Consumption of the grain has also been reported to reduce the risk of cancer (Subastri et al, 2015) and help to lower cholesterol levels (Table 6) (Asharani et al, 2010). Finger millet starch is used in the pharmaceutical industries as a binder for the preparation of granules and capsule dosage forms (Shiihii et al, 2011).…”
Section: Nutritional Antioxidant Properties and Potential Health Benmentioning
confidence: 99%
“…Fermentation increases the nutritional value, total reducing and nonreducing sugars, and significantly affects the protein, vitamins, minerals and fat concentration (Khetarpaul and Chauhan, 1990). It also increases the total phenols, total flavonoids, free amino acids and other phytochemical components (Subastri et al, 2015). Fermented foods are popular because they lower the amount of anti-nutrients such as tannins, phytic acids and trypsin inhibitors.…”
Section: Fermentationmentioning
confidence: 99%